Efektivitas Penggunaan Google Form Berbasis Android Sebagai Media Asesmen Akhir Semester Pada Mata Pelajaran Fiqih - Setiawan S; Rosidin R; Nani Rohayani; Cecep Firdaus; Mad Ali; Fitriyani Kosasih; Ifah Khadijah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the implementation procedure and analyze the effectiveness of using Android-based Google Forms as a media for Semester Final Assessment (PSAS) in Fiqh subjects for grade VIII at MTs Al-Fatah Kutawaringin. The method used is descriptive quantitative with 40 students as research subjects. Data collection techniques include tests via Google Form, observation, interviews, and documentation. The results showed that the average score of students was 82.25 with a learning completeness rate of 72.5%. The use of Google Forms proved effective in increasing the efficiency of correction time, objectivity of assessment, and ease of processing learning outcome data. However, the main obstacles faced were dependence on internet networks and the need for manual correction for essay-type questions.